Capacity building for trade impact assessment : lessons from the development of environmental impact assssment - George, Clive (2001)
Examines difficulties in creating capacity to undertake impact assessments of trade policy and possible approaches to overcoming them, particularly in developing countries. Reviews experiences with environmental impact assessment capacity-building. Considers how the lessons learned might be applied to initiatives to build capacity for the impact assessment of trade policy.